A study on regulatory bases of psychological students' success at examinations - V I Morosanova; E V Filippova (RUDN Journal of Psychology and Pedagogics, 2009)
The article discusses the aspects of psychological students' success at examinations. The author analyses traits of character that are necessary for passing final examinations.